Feedback, Performance, and Accountability: A Quantitative Study of Government Valuers in Non-Ministry of Finance Institutions - Riyanto, Edy; Nurbiyanto; Murwanto, Nugroho Yoni (Yayasan Ilomata, 2025)
This study evaluates the effectiveness of the Government Functional Valuer Position outside the Ministry of Finance in supporting state asset management. Using a quantitative approach based on a Likert scale, this research analyzes key variables such as Key Performance Indicators (KPIs), Return on Investment (ROI), Feedback and Evaluation, Benchmarking, Productivity, and Job Satisfaction. Data was collected through questionnaires distributed to valuers and related stakeholders in regional government agencies. The results show that Feedback and Evaluation have a significant impact on Productivity (r = 0.942), emphasizing the importance of feedback mechanisms in optimizing valuer performance. Additionally, Benchmarking is closely related to Job Satisfaction (r = 0.923), indicating that implementing global standards contributes to improved motivation and work quality. However, the KPI and ROI variables, while conceptually relevant, do not show a statistically significant impact on Productivity. This study recommends strengthening feedback systems, adopting best practices through benchmarking, and enhancing training programs to improve valuers' technical competencies. These policy implementations are expected to improve efficiency and accountability in managing state assets.